Understanding and Modeling Förster-type Resonance Energy Transfer (FRET) : FRET-Applications, Vol. 3 /: FRET-Applications, Vol. 3. (2017) - Demir, Hilmi Volkan; Hernández Martínez, Pedro Ludwig; Govorov, Alexander
No abstract available